Understanding of history and some of its programmes in Malaysia - Dato’ Hj Zainol Rashid, Zahidi (Persatuan Pustakawan Malaysia, 2012)
Evidence shows that not all documented records are thorough and adequately recorded. Gaps still exist in history. Collections of personal papers may be weak in the information on the formative years of the donors. Letters or correspondence do not necessarily potray an author's inner thoughts and may be misleading to the researchers. It is within this context that oral history is regarded and is a necessity rather that a luxury and indeed a help in dealing with the modern mountain of paper.